Towards a management theory for introduction of IT innovations in top level sports - Ghorbani, M.; Lames, M. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
Recent years have seen an increasing number of introduction of IT innovations in top level sports in almost each competitive nation. Practical experiences show that it is a long way with many pitfalls leading from a technological innovation to its successful introduction in sports. The idea of this paper is to make use of management concepts brought forward in economy to provide a conceptual framework for this task. The benefit would be to circumvent common problems, to prepare innovators for typical ones and to improve each stakeholder`s understanding of the process. Product and innovation life cycle theory, innovation management theory, and customer relationship management theory are described in the paper. Applicability to the problem under investigation is discussed, and important contributions as well as conceptual differences are pointed out. As examples for best practice, two IT innovations introduced recently in German top level sports are analyzed. National teams (male and female) in the Paralympic sport goalball and Olympic beach-volleyball introduced a computer based match analysis system. One may conclude that it is helpful to borrow conceptual knowledge from economy to better understand the introduction of IT innovations in top level sports.